Do green indices outperform BSESENSEX and energy indices in India? Some evidence on investors' commitment towards green investing - Debabrata Mukhopadhyay; Nityananda Sarkar (International Econometric Review (IER), 2021)
This study has examined the performance of two Indian stock indices capturing the commitment of industries towards mitigating risks arising from pollution and climate change viz., BSE Greenex and BSE Carbonex, vis- a-vis two indices augmenting carbon emissions - BSE Energy index and BSE Oil & Gas index, and also BSESNSEX, the apex index representing Indian stock market, during the period January 2010 to December 2019. Besides using three risk-adjusted return ratios, namely, the Sharpe ratio, Treynor ratio, and Jensen's Alpha, on all the five indices, we have also applied GARCH-in-mean model to find if there is a risk premium involved either for causing emission or for mitigating the ill effects of emission. The results show that BSE Carbonex outperforms BSESENSEX and all the three other indices in terms of the three-performance metrics. Moreover, the two green indices and BSESENSEX show significant presence of risk premium in the framework of GARCH-in-mean model while risk premium is insignificant in case of the two carbon emitting energy indices. Overall, therefore, the study finds that some of the green funds such as those representing BSE Carbonex outperform the investors' benchmark stock index BSESENSEX and the two energy indices which represent traditional funds in India. A brief look at the term structure of return and risk also gives support to the green investing index BSE Carbonex. The findings of this study thus advocate for carbon-efficient practices among the larger business entities in India even after addressing the environmental, social and governance issues of responsible investing.
Keywords: C32; G11; Q40; Q54; 330; Energy Indices; Green Indices; GARCH-In-Mean Model; Risk-Return Relationship